HUBUNGAN ANTARA MINAT BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIS DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IX SMP NEGERI SATU ATAP 1 MERANGIN - Kurnia Illahi; Yohanes; Sukur (Matedukasia, 2023)
The background of this study is students who are less interested in learning mathematics which has an impact on understanding mathematical concepts and mathematical conundrum-solving skills of the class IX pupils from Merangin One Roof 1 Public Middle School in the 2022/2023 Academic Year. The purpose of this study is to explain the connection or significance between a desire to learn and awareness of mathematical concepts and The ability of SMP Negeri pupils in class IX to solve mathematical problems One Roof 1 Merangin. This study involved 3 variables, namely interest in learning as the variable that is independent and the understanding of mathematical concepts and ability to solve mathematical problems as the dependent variable. In this investigation, the population consisted of class IX pupils at One Roof Middle School Public 1 Merangin for the academic year 2022–2023. The method of sampling made use of a total sampling method, namely all students in class IX consisting of 1 class totaling 30 pupils—data gathering with tests and survey methods. The instrument use was in the form of 34 statement items, 1 item about understanding mathematical concepts, and 1 item about mathematical problem-solving ability. Data analysis utilized to evaluate the theory employs the Pearson product-moment correlation technique, to test the significance using the Z-test, followed by the determining coefficient formula to express the size of the contribution With relation to variable Y from data analysis reveals that Z_count> Z_table or 2.202 > 1.960, after which H_0 is turned down and H_1 is approved. meaning that A strong correlation exists between learning interest understanding of mathematical concepts and the capacity for solve quantitative problems kids in class IX of One Roof Public Middle School 1 Merangin for the 2022/2023 academic year.